2007
DOI: 10.1152/jn.00429.2007
|View full text |Cite
|
Sign up to set email alerts
|

Internal Spatial Organization of Receptive Fields of Complex Cells in the Early Visual Cortex

Abstract: Sasaki KS, Ohzawa I. Internal spatial organization of receptive fields of complex cells in the early visual cortex. J Neurophysiol 98: 1194 -1212, 2007. First published July 25, 2007; doi:10.1152/jn.00429.2007. The receptive fields of complex cells in the early visual cortex are economically modeled by combining outputs of a quadrature pair of linear filters. For actual complex cells, such a minimal model may be insufficient because many more simple cells are thought to make up a complex cell receptive field.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
27
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 39 publications
9
27
1
Order By: Relevance
“…The geometric mean of the pooling ratio amounted to 1.80 for the Y direction and 1.30 for the X direction for our sample of complex cells. Sasaki and Ohzawa (2007) reported that the majority of complex cells in the early visual cortex pool subunits minimally in space to make up the monocular RFs (median of size ratio, ϳ1.21 in area), concluding that complex cells can be described adequately by the standard energy model without spatial pooling (Adelson and Bergen, 1985;Qian 1994;Fleet et al, 1996). An apparent contradiction with this report can be explained by a difference in the metric for evaluating the degree of spatial pooling.…”
Section: Spatial Pooling Of Binocular Disparity Detectorscontrasting
confidence: 61%
See 2 more Smart Citations
“…The geometric mean of the pooling ratio amounted to 1.80 for the Y direction and 1.30 for the X direction for our sample of complex cells. Sasaki and Ohzawa (2007) reported that the majority of complex cells in the early visual cortex pool subunits minimally in space to make up the monocular RFs (median of size ratio, ϳ1.21 in area), concluding that complex cells can be described adequately by the standard energy model without spatial pooling (Adelson and Bergen, 1985;Qian 1994;Fleet et al, 1996). An apparent contradiction with this report can be explained by a difference in the metric for evaluating the degree of spatial pooling.…”
Section: Spatial Pooling Of Binocular Disparity Detectorscontrasting
confidence: 61%
“…Procedures for animal preparation and maintenance, surgery, single-unit recording, and experiment setup have been described in detail previously (Sasaki and Ohzawa, 2007). Only a brief account is provided here, with an emphasis on those aspects of the methodology most relevant to the present study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Spatial frequency and orientation tunings were measured by subspace reverse correlation using rapidly flashed grating stimuli (Nishimoto et al 2005;Ringach et al 1997a). Dense-noise stimulus was presented to obtain receptivefield (RF) maps of CRF (linear kernel) using standard reverse correlation (Sasaki and Ohzawa 2007). Orientation and spatial-frequency tunings were also obtained using conventional drifting grating stimuli.…”
Section: Methodsmentioning
confidence: 99%
“…The shape (aspect ratio) and number of receptive fi eld subregions are major factors that affect the tuning width [18][19][20] . Orientation selectivity is also associated with a broader range of stimulus values (global measure).…”
Section: Introductionmentioning
confidence: 99%